Effect of Market Penetration Strategy on Sales Growth of Coffee Export in Kenya - Muriuki, Ninah Makena; Muema, Wilson; Rintari, Nancy (International Journal of Professional Practice, 2023)
Kenya is one of the leading coffee exporters in the world. In July 2021, the number of coffee export sales in Kenya was recorded at 1.2 thousand metric tons, showing a significant recovery from the previous months. This recovery increased the auction price to $ 6.23 /kilogram, up from $ 5.5/kilogram. However, coffee sector has experienced a boom and bust in the past two decades. Unlike horticultural products whose prices remain constant for an economically significant period, the prices for coffee products have been fluctuating. The global market is highly volatile and the question is: could coffee market instability be a result of changes in consumer preferences, supply-demand trends, and unpredictable prices of coffee products? It would be interesting to establish whether a market penetration strategy could solve these issues, and make coffee business predictable. The study sought to evaluate the effect of market penetration strategy on sales growth of coffee export in Kenya, using a cross-sectional survey design. The target population was 157 coffee marketing firms in Kenya. A sample size of 384 respondents was selected using stratified random sampling. Analysis of data utilized Spearman correlation analysis and binary logistic regression. Results revealed a strong and positive correlation (r = .672, p-value = 0.000) at a significance level of 0.01 between market penetration strategies and the sales growth of coffee exporters in Kenya. Thus concluding that market penetration strategy significantly affected the sales growth of coffee exports in Kenya. Further, exporters were recommended to develop a market penetration strategy tailored to Kenyan coffee market to establish a clear understanding and potential for coffee exports. Additionally, an analysis of the country's coffee consumption habits and trends and an assessment of the competitiveness of the Kenyan coffee industry to promote the growth of coffee export from Kenya need to be carried.